HUBUNGAN KECERDASAN EMOSIONAL DENGAN KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DASAR NEGERI SE-KELURAHAN LAMOKATO KECAMATAN KOLAKA KABUPATEN KOLAKA - Akbar, Muh.; Suardi; Latang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem in this study is the lack of understanding and empirical data on the relationship between emotional intelligence and learning leadership at the elementary school level. The general objective of this study is to analyze the relationship between emotional intelligence and the learning leadership of elementary school principals in Lamokato Village, Kolaka District, Kolaka Regency. The research method used is Quantitative ex post facto. Data collection techniques use Likert scale questionnaires. Data analysis techniques use descriptive statistics and inferential statistics. Based on the results of the product moment test, a significance value of = 0.000 is obtained, which is smaller than  = 0.05, indicating a significant relationship between emotional intelligence and the principal's learning leadership